(untitled) (Web of Teachers: Inderscience Research, 2024)
Time, as a core construct of human cognition, plays a pivotal role in linguistic and pragmatic practices. This study examines the interaction of time with temporal deixis, tense-aspect systems, and culturally embedded temporal cognition, highlighting how time is encoded in language and employed to structure discourse, align intentions, and aid comprehension.Using cross-linguistic data from English and Uzbek, the study reveals universal tendencies, such as temporal deixis ensuring coherence, and language-specific differences, including variations in temporal markers and cultural perceptions. Findings demonstrate that time functions as a multidimensional linguistic construct, integrating cognitive, grammatical, and cultural elements to create meaning in communication. This research advances understanding of time as a central dimension in linguistic and pragmatic analysis.